ANALISIS IMPLEMENTASI ANGGARAN BERBASIS KINERJA TERHADAP AKUNTABILITAS KINERJA PEMERINTAH KABUPATEN PEGUNUNGAN BINTANG - Prayoga, Vicky Antonio; Rofingatun, Siti; Daat, Sylvia Christina (Jurnal Akuntansi, Audit, dan Aset, 2020)
The objective of this study is to observe the influence of performance-based budgeting (PBB) on thegovernment's accountability, such as planning, implementation, accountability, and performanceevaluation. Pegunungan Bintang was chosen as a research location and the cluster sampling method was used to determined 96 respondents. Data processing technique consist of several stages, first stage isdata quality test by used validity test and reliability test, next step was normality test,multicollinearity test dan heteroscedasticity test called classical assumption test, when researchdata was valid and reliable and normally distributed, there was no multicollinearity danheteroscedasticity, then hypothesis test worth to continue. Hypothesis test consisted of multiplelinear regression, determination coefficient (R2), partial tested (t-test), and simultaneous tested (Ftest).The result shows that partially the planed and implementation have no effect on accountability ofgovernment’s performance accountability with significance values of 0.872 and 0.656 respectively,however accountability and performance evaluation had an effect on the government’s performanceaccountability with significance values of 0,000 and 0,000.